2001
DOI: 10.1073/pnas.061337998
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo propagation of infectious sheep scrapie agent in heterologous epithelial cells expressing ovine prion protein

Abstract: Transmissible spongiform encephalopathies, or prion diseases, are fatal degenerative disorders of the central nervous system that affect humans and animals. Prions are nonconventional infectious agents whose replication depends on the host prion protein (PrP). Transmission of prions to cultured cells has proved to be a particularly difficult task, and with a few exceptions, their experimental propagation relies on inoculation to laboratory animals. Here, we report on the development of a permanent cell line su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
264
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(277 citation statements)
references
References 58 publications
9
264
0
4
Order By: Relevance
“…Recent studies confirmed the original finding [146] that non-neuronal cell lines can efficiently propagate prions. Common fibroblast cell lines [147] and a microglial cell line (MG20) established from transgenic mice overexpressing PrP are susceptible to various murine prion strains [61].…”
Section: Cell Models Permissive To Experimental Rodent-adapted Scrapsupporting
confidence: 65%
See 4 more Smart Citations
“…Recent studies confirmed the original finding [146] that non-neuronal cell lines can efficiently propagate prions. Common fibroblast cell lines [147] and a microglial cell line (MG20) established from transgenic mice overexpressing PrP are susceptible to various murine prion strains [61].…”
Section: Cell Models Permissive To Experimental Rodent-adapted Scrapsupporting
confidence: 65%
“…The epithelial rabbit RK13 cell line, expressing no detectable endogenous rabbit PrP C , was genetically engineered to stably express an ovine PrP C variant ( 136 V 154 R 171 Q) associated with a very high susceptibility to scrapie [59]. The resulting cultures, known as Rov cells, can be readily infected with and replicate to high titres some sheep scrapie isolates [146]. Neuroglial cell lines with Schwann-like features [3] and primary cultures of neurons and astrocytes [34], both of which were derived from transgenic mice expressing the VRQ allele of ovine PrP C , were later shown to be permissive to sheep scrapie as well.…”
Section: Cell Models Propagating Naturally-occurring Prion Isolatesmentioning
confidence: 99%
See 3 more Smart Citations